2022
DOI: 10.33889/ijmems.2022.7.5.048
|View full text |Cite
|
Sign up to set email alerts
|

A Lot-Sizing Model for a Multi-State System with Deteriorating Items, Variable Production Rate, and Imperfect Quality

Abstract: Conventional production systems assume that during the manufacturing processes, machines operate without breakdown over an infinite planning horizon and manufacture only products of good quality. Imperfect production processes as a result of machine degradation are common in manufacturing. This paper deals with a problem that concerns the modelling and evaluation of the performance of a multi-state production system that is subject to degradation and its effect on lot sizing. Here, we consider that the cycle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This paper introduces an extended inventory model for deteriorating items that specifically incorporates the influence of product freshness on demand. The model builds upon the work of Tshinangi et al (2022) and extends this research by considering the dynamic relationship between the concept of shifting production rates in a deteriorating process and both freshness condition and deterioration of products, guided by Banerjee and Agrawal (2017). Initially, the demand for the product (e.g., meat) is determined solely by its selling price and its displayed stock level when it is fresh.…”
Section: Research Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper introduces an extended inventory model for deteriorating items that specifically incorporates the influence of product freshness on demand. The model builds upon the work of Tshinangi et al (2022) and extends this research by considering the dynamic relationship between the concept of shifting production rates in a deteriorating process and both freshness condition and deterioration of products, guided by Banerjee and Agrawal (2017). Initially, the demand for the product (e.g., meat) is determined solely by its selling price and its displayed stock level when it is fresh.…”
Section: Research Contributionmentioning
confidence: 99%
“…They demonstrated that process deterioration could be the result of minor stoppages and speed losses, which in practice may affect the efficiency of the process. Tshinangi et al (2022) conducted a study focusing on a degrading production system that incorporates shifting production rates, imperfect quality, and partial backlogging of demand along with lost sales to understand the impact of these factors on system performance, such as inventory levels, cycle time, shortage levels and overall cost incurred.…”
Section: Introductionmentioning
confidence: 99%